The Some Properties of Beta Hat Generalized Closed Set in Generalized Topological Spaces - Camargo, John Ferwin Zamora (International Journal For Research In Mathematics And Statistics, 2019)
This study introduced the concept of beta hat generalized closed set in generalized topological spaces. It also investigated related concepts such as - -interior and - -closure of a set. This paper proved that every -open (resp. -closed) set is - -open (resp. - -closed). It is also shown that the family of all - -open subsets in X does not always form a generalized topology in X. Moreover, - -closure of set is smaller than -closure while the - -interior is generally larger than its -interior.